The quality of working life: gap between perception and idealization impact of gender and status - Salès-Wuillemin, Edith; Minondo-Kaghad, Brigitte; Chappé, Julien; Gélin, Morgan; Dolard, Adrien (Frontiers in Psychology, 2023)
The aim of this study was to measure the quality of working life (QWL) perceived by employees according to their gender (Women vs. Men) and their status (Managers vs. Co-workers). A questionnaire was distributed to 1321 employees. It comprised two scales: the WRQoL scale and the QUALTRA-scale. The QUALTRA-scale enables the calculation of an index δ that measures the difference between the perceived QWL and the ideal QWL. The ANOVA revealed an impact of status on the perceived QWL on both scales. There was no gender effect. However, there was an effect of both gender and status on the index δ of the QUALTRA-scale. For the Women group and the Coworker group, δ was higher for the dimensions of Tasks and Work Organization, Recognition and Organizational Support, and Professional Development. In particular, for the Women group, δ was higher for the Social Relationships at Work dimension whereas for the Co-workers, it was higher for the Work Environment dimension. These results are discussed, highlighting the value of measuring the ideal QWL as a reference point for assessing the QWL.